Curing coating for vacuum lamination of electric equipment shell and preparation method of curing coating

By using the lip ring epoxy resin, cationic light cause, and cedic thermal cause of the vacuum fusion of the vacuum coatings, the coating of the electrical equipment shell shell film and the substrate are achieved, and the coatings are easy to yellow and environmental performance. Low problems provide dual solidification and high -environmental performance solutions.

CN119351021APending Publication Date: 2025-01-24SHENZHEN WANLI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411845813.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the prior art, during the bonding process of the diaphragm and substrate of the electrical equipment shell, the coating is prone to yellowing, its appearance is affected, its curing method is single, and its environmentally friendly performance is low.

Method used

A vacuum -fitting coating is used, including the fat rings epoxy resin, cationic light cause, and cationic thermal cause, and solidify through the dual way of curing and thermal solidification to avoid volatile harmful gases and improve environmental performance.

Benefits of technology

It improves the anti-yellowing performance of the coating, improves the appearance durability of the electrical equipment casing, provides a variety of curing methods, and enhances the environmental protection performance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351021A_ABST
    Figure CN119351021A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of shells of electrical equipment, manufacturing of synthetic materials, curing coatings and the like, and provides an electrical equipment shell, a curing coating for vacuum lamination and a preparation method thereof.The electrical equipment shell comprises a base material and a membrane with a decorative effect, and the base material and the membrane are laminated through the curing coating for vacuum lamination under the vacuum condition; the curing coating for vacuum lamination comprises alicyclic epoxy resin, a cationic photoinitiator and a cationic thermal initiator, the weight percentage of the alicyclic epoxy resin is 60-77%, the weight percentage of the cationic photoinitiator is 22-39%, and the weight percentage of the cationic thermal initiator is 0.1-1%. The curing coating for vacuum lamination supports multiple curing modes of photocuring and thermocuring, does not volatilize harmful gas, and is high in environmental protection performance. An electrical equipment shell prepared by laminating a diaphragm and a base material with the curing coating for vacuum lamination is high in yellowing resistance, and the appearance visual experience of the electrical equipment shell is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical fields of housing of electric equipment, manufacture of synthetic materials, curing coatings and the like, and in particular to a housing of electric equipment, curing coating for vacuum lamination and a preparation method thereof. Background Art

[0002] In the shell appearance design and production of electronic devices such as mobile phones and tablets, as well as automotive interior parts, in order to meet consumers' demand for shell appearance, the shell is usually designed to be transparent and combined with a diaphragm with decorative effects to enhance the aesthetics of the device. Among them, the diaphragm with decorative effects needs to be bonded to the shell substrate under vacuum conditions. In order to achieve the bonding between the shell substrate and the diaphragm, an adhesive is required. The adhesives used in the prior art are mostly ordinary liquid coatings, which are easy to turn yellow, affecting the appearance of the shell, and ordinary liquid coatings have a single curing method. Many ordinary liquid coatings also volatilize harmful gases and have low environmental performance.

[0003] In summary, in the prior art, the bonding technology of the diaphragm and substrate of the housing of electrical equipment has technical problems such as the paint is easy to yellow, the appearance of the housing is easily affected, the paint curing method is single, and the environmental protection performance is low. Summary of the invention

[0004] In view of the deficiencies in the above-mentioned prior art, the present invention provides a curing coating for electrical equipment housing and vacuum bonding and a preparation method thereof, so as to improve the anti-yellowing performance of the coating, improve the durability of the housing appearance, provide a variety of coating curing methods, and improve the environmental performance of the coating.

[0005] In a first aspect, the present invention provides an electrical equipment casing, which comprises a substrate and a diaphragm with a decorative effect, wherein the substrate and the diaphragm are bonded together under vacuum conditions by a vacuum bonding curing coating; the vacuum bonding curing coating comprises: an alicyclic epoxy resin, a cationic photoinitiator and a cationic thermal initiator; the weight percentage of the alicyclic epoxy resin is 60-77%, the weight percentage of the cationic photoinitiator is 22-39%, and the weight percentage of the cationic thermal initiator is 0.1-1%.

[0006] In a second aspect, the present invention provides a curing coating for vacuum bonding, comprising: an alicyclic epoxy resin, a cationic photoinitiator and a cationic thermal initiator; the weight percentage of the alicyclic epoxy resin is 60-77%, the weight percentage of the cationic photoinitiator is 22-39%, and the weight percentage of the cationic thermal initiator is 0.1-1%.

[0007] In a third aspect, the present invention provides a method for preparing a curing coating for vacuum lamination, comprising: Add the cationic thermal initiator to the cationic photoinitiator and stir evenly in the dark to obtain a mixture of the two cationic initiators; Adding the mixed two cationic initiators into the alicyclic epoxy resin as a whole and stirring evenly to obtain a solidified coating as a whole; The entire cured coating is subjected to vacuum degassing to obtain the cured coating for vacuum lamination.

[0008] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides an electrical equipment housing, a curing coating for vacuum bonding and a preparation method thereof. The electrical equipment housing comprises a substrate and a diaphragm with a decorative effect. The substrate and the diaphragm are bonded together under vacuum conditions by a curing coating for vacuum bonding; the curing coating for vacuum bonding comprises: alicyclic epoxy resin, a cationic photoinitiator and a cationic thermal initiator; the weight percentage of the alicyclic epoxy resin is 60-77%, the weight percentage of the cationic photoinitiator is 22-39%, and the weight percentage of the cationic thermal initiator is 0.1-1%. The curing coating for vacuum bonding supports multiple curing methods such as light curing and thermal curing, does not volatilize harmful gases, and has high environmental protection performance. The electrical equipment housing prepared by bonding the diaphragm and the substrate with the curing coating for vacuum bonding has high anti-yellowing performance, and the appearance and visual experience of the electrical equipment housing is good. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Some specific embodiments of the present invention will be described in detail in an exemplary and non-restrictive manner with reference to the drawings. The same reference numerals in the drawings indicate the same or similar components or parts. It should be understood by those skilled in the art that these drawings are not necessarily drawn to scale. In the drawings: Figure 1 It is a schematic flow chart of a method for preparing a curing coating for vacuum lamination according to an embodiment of the present invention. DETAILED DESCRIPTION

[0010] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is only an embodiment of a part of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work should fall within the scope of protection of the present invention.

[0011] Embodiment 1 See also Figure 1This embodiment provides an electrical device housing, the electrical device housing includes a substrate and a film with a decorative effect, the substrate and the film are bonded together under vacuum conditions by a vacuum bonding curing coating; the vacuum bonding curing coating includes: alicyclic epoxy resin, cationic photoinitiator and cationic thermal initiator; the weight percentage of the alicyclic epoxy resin is 60-77%, the weight percentage of the cationic photoinitiator is 22-39%, and the weight percentage of the cationic thermal initiator is 0.1-1%. When producing the vacuum bonding curing coating, the following specific implementation methods can be used.

[0012] Embodiment 1, the weight percentage of the alicyclic epoxy resin is 60%, the weight percentage of the cationic photoinitiator is 39%, and the weight percentage of the cationic thermal initiator is 1%. Add the cationic thermal initiator to the cationic photoinitiator and stir evenly in the dark to obtain the two mixed cationic initiators as a whole; add the two mixed cationic initiators as a whole to the alicyclic epoxy resin and stir evenly to obtain the cured coating as a whole; vacuum degas the cured coating as a whole to obtain the cured coating for vacuum bonding. In this embodiment, a tensile test can be performed according to the GB / T 2567-2008 standard, and a tensile testing machine is used to measure the various properties of the bonded samples of the substrate and the diaphragm when subjected to force. For example, the tensile strength, tensile elastic modulus, elongation at break, etc. of the bonded sample when subjected to force are measured. The following experimental data and properties of the bonded sample are obtained through the test, specifically: tensile strength 70-80 MPa, tensile elastic modulus 3000-4000 MPa, elongation at break 3-6%. Among them, the tensile strength is 70-80 MPa, which indicates the maximum stress that the laminated sample can withstand when subjected to tensile force. The alicyclic epoxy resin itself has a high mechanical strength, and the high tensile strength indicates that the laminated sample has a strong tensile resistance. The tensile elastic modulus is 3000-4000 MPa, which reflects that the elastic deformation ability of the laminated sample under tensile stress has sufficient rigidity and elastic stability. The application of alicyclic epoxy resin ensures a higher modulus value, which is conducive to ensuring the durability and structural stability of the shell. The elongation at break is the percentage that the laminated sample can be extended before breaking, indicating the ductility or flexibility of the laminated sample. The elongation at break of 3-6% indicates the ductility or flexibility of the laminated sample. The alicyclic epoxy resin can improve ductility to a certain extent, prevent brittle fracture during the lamination process, and help maintain the firm bonding between the diaphragm and the substrate. In addition, in the present embodiment, the bending resistance of the laminated sample can be recorded by testing in accordance with the GB / T 2567-2008 standard by a three-point or four-point bending tester. For example, the bending strength and bending elastic modulus of the bonded sample. The bending strength reflects the maximum stress that the bonded sample can withstand when bent. A bending strength of 130-150 MPa indicates that the bonded sample has a strong bending resistance when bent, ensuring the ability to withstand bending in practical applications and avoiding deformation of the shell after bonding. The bending elastic modulus is used to measure the rigidity of the bonded sample when bent. A bending elastic modulus of 3000-4000 MPa indicates that the coating has good elastic properties after light or heat curing, which is consistent with the characteristics of alicyclic epoxy resins and ensures the shape stability of the shell. In addition, in this embodiment, the impact strength can be measured by an impact testing machine according to GB / T 2567-2008 standard to test the fracture behavior of the bonded sample when impacted. A differential scanning calorimeter (DSC) is used to measure the glass transition temperature of the bonded sample according to IEC 61006 standard.Impact strength reflects the ability of the bonded sample to resist impact or rapid force. An impact strength of 10-20 kJ / m² indicates that the bonded sample will not break easily when subjected to external impact, showing excellent impact resistance, which helps to improve the durability of the shell. The glass transition temperature (DSC) measures the temperature range in which the bonded sample changes from a rigid glass state to a rubber state. A glass transition temperature of 90-110°C indicates that the bonded sample has a higher glass transition temperature, ensuring that the bonded sample maintains structural stability and excellent mechanical properties within the daily use temperature range. Among them, alicyclic epoxy resins have a higher glass transition temperature, ensuring that the bonded sample maintains structural stability and excellent mechanical properties within the daily use temperature range.

[0013] Embodiment 2, the weight percentage of the alicyclic epoxy resin is 77%, the weight percentage of the cationic photoinitiator is 22%, and the weight percentage of the cationic thermal initiator is 1%. The cationic thermal initiator is added to the cationic photoinitiator and stirred evenly in the dark to obtain the two mixed cationic initiators as a whole; the two mixed cationic initiators as a whole are added to the alicyclic epoxy resin and stirred evenly to obtain the cured coating as a whole; the cured coating as a whole is vacuum degassed to obtain the cured coating for vacuum bonding. It should be noted that according to the GB / T 2567-2008 standard, the tensile properties of the substrate and the film bonding sample are tested using a tensile testing machine, including tensile strength, tensile elastic modulus and elongation at break. The experimental data obtained a tensile strength of 85-95MPa, indicating that after increasing the content of the alicyclic epoxy resin, the bonded sample exhibits a higher tensile resistance and can withstand greater tensile stress. The tensile elastic modulus is 3500-4500MPa, indicating that the sample has better rigidity and elastic stability under tensile stress, further improving the structural stability of the bonded sample. The elongation at break is 2.5-5%, indicating that the ductility or flexibility of the sample is slightly reduced due to the increase in the proportion of alicyclic epoxy resin, but it still has sufficient resistance to brittle fracture. The bending properties of the bonded samples were measured using a three-point or four-point bending tester in accordance with the GB / T2567-2008 standard, and the bending strength was 140-160MPa, indicating that the bonded samples showed stronger bending resistance when bent, ensuring better bending resistance in practical applications and avoiding deformation of the shell after bonding. The bending elastic modulus is 3500-4500 MPa, indicating that the increase in the proportion of alicyclic epoxy resin further improves the rigidity and elastic properties of the sample, ensuring the shape stability and durability of the shell. According to the GB / T 2567-2008 standard, the impact strength of the bonded samples was measured by an impact tester, and the impact strength was 12-22 kJ / m², indicating that the bonded samples have higher impact resistance, can better resist external impact, and further improve the durability of the shell. Using a differential scanning calorimeter (DSC), the glass transition temperature of the bonded sample was measured in accordance with the IEC 61006 standard, and the glass transition temperature was 95-115°C, indicating that the sample has excellent structural stability and mechanical properties within the daily use temperature range. The increase in the proportion of alicyclic epoxy resin further improves its heat resistance and ensures the stability of the bonded sample in a high temperature environment. In general, Implementation 2 can significantly improve the mechanical strength and rigidity of the bonded sample by increasing the proportion of alicyclic epoxy resin, especially in terms of tensile strength, flexural strength and glass transition temperature.

[0014] Embodiment 3, the weight percentage of the alicyclic epoxy resin is 77%, the weight percentage of the cationic photoinitiator is 22.9%, and the weight percentage of the cationic thermal initiator is 0.1%. The cationic thermal initiator is added to the cationic photoinitiator and stirred evenly in the dark to obtain the two mixed cationic initiators as a whole; the two mixed cationic initiators as a whole are added to the alicyclic epoxy resin and stirred evenly to obtain the cured coating as a whole; the cured coating as a whole is vacuum degassed to obtain the cured coating for vacuum bonding. It should be noted that according to the GB / T 2567-2008 standard, the tensile properties of the bonded sample are tested, including tensile strength, tensile elastic modulus and elongation at break, and the tensile strength is 80-90MPa, indicating that the proportion of the alicyclic epoxy resin remains high (77%), but the adjustment of the cationic photoinitiator and the thermal initiator slightly reduces the tensile strength of the sample, and still has excellent tensile resistance. The tensile elastic modulus is 3400-4400MPa, indicating that the rigidity and stability of the bonded sample under tensile stress are still excellent. The elongation at break is 3-5%, indicating that the ductility and flexibility of the sample before fracture are at a moderate level, which can effectively prevent brittle fracture. In addition, the bending properties of the bonded samples were tested by a three-point or four-point bending tester, and the bending strength was 135-155MPa, indicating that the samples have sufficient bending resistance and are suitable for occasions requiring certain structural support. The bending elastic modulus is 3300-4300 MPa, indicating that the samples have good elastic properties under bending stress and can maintain shape stability in actual use. According to GB / T 2567-2008 standard, the impact strength of the bonded samples was measured using an impact tester, and the impact strength was 10-18 kJ / m². The impact resistance was slightly reduced, but it still showed a certain ability to resist external impact, meeting the requirements of daily applications. Using a differential scanning calorimeter (DSC), according to the IEC 61006 standard, the glass transition temperature of the bonded samples was measured, and the glass transition temperature was 92-112℃, showing a higher glass transition temperature, ensuring the structural stability of the samples at room temperature and higher temperature ranges. In summary, Embodiment 3 further adjusts the ratio of cationic photoinitiator and thermal initiator to make the curing reaction process more balanced. Although the tensile strength and impact resistance are slightly lower than those of Embodiment 2, the sample still maintains excellent mechanical properties and thermal stability, especially in terms of glass transition temperature and bending properties. This formula is suitable for applications that have high requirements for durability and flexibility, and are sensitive to economic and process requirements.

[0015] Embodiment 4, the weight percentage of the alicyclic epoxy resin is 65%, the weight percentage of the cationic photoinitiator is 34.5%, and the weight percentage of the cationic thermal initiator is 0.5%. The cationic thermal initiator is added to the cationic photoinitiator and stirred evenly in the dark to obtain the two mixed cationic initiators as a whole; the two mixed cationic initiators as a whole are added to the alicyclic epoxy resin and stirred evenly to obtain the cured coating as a whole; the cured coating as a whole is vacuum degassed to obtain the cured coating for vacuum bonding. It should be noted that according to the GB / T 2567-2008 standard, the tensile strength, tensile elastic modulus and elongation at break of the bonded sample are measured using a tensile testing machine, and the tensile strength is 75-85MPa, indicating that the tensile strength is reduced, and the bearing capacity of the sample under the tensile force is slightly reduced, but it still meets the requirements of most practical applications. The tensile elastic modulus is 3100-4000MPa, and the elastic modulus is slightly lower than that of embodiment 3, reflecting that the rigidity of the sample is reduced, but it still maintains a certain stability. The elongation at break is 4-7%, reflecting that the elongation at break is slightly higher than other implementation methods, indicating that the sample has better ductility and flexibility, and is more superior in preventing brittle fracture. The bending properties are measured by a three-point or four-point bending tester, and the bending strength is 120-140MPa, showing a certain decrease, which is suitable for occasions with medium requirements for bending resistance. The bending elastic modulus is 3000-3900 MPa, reflecting that the decrease in the bending elastic modulus is related to the reduction in the proportion of alicyclic epoxy resin in the formula, but the overall performance can still meet the actual application requirements. According to GB / T 2567-2008 standard, the impact strength of the bonded sample is measured by an impact tester, and the impact strength is 12-20 kJ / m², reflecting that the impact strength is well maintained, indicating that the sample has good resistance to external impact and can effectively resist external forces. The glass transition temperature was measured using a differential scanning calorimeter (DSC) according to the IEC 61006 standard, and the glass transition temperature was 85-105°C, which showed that the glass transition temperature was slightly lower, indicating that the stability of the sample at high temperature was reduced, but it could still maintain good mechanical properties within the general use temperature range. In general, Implementation 4 can improve the ductility and flexibility of the sample during the curing process by increasing the proportion of cationic photoinitiator and reducing the proportion of alicyclic epoxy resin, but it has a decrease in tensile strength and rigidity.

[0016] It should be generally explained that alicyclic epoxy resin is used in this embodiment, and this type of resin has higher weather resistance and anti-yellowing properties compared with traditional linear epoxy resin. Alicyclic epoxy resin is not easy to turn yellow due to the influence of light or heat in long-term use, thereby maintaining the transparency and aesthetics of the shell. In addition, in this embodiment, the vacuum bonding curing coating contains a cationic photoinitiator and a cationic thermal initiator, which indicates that the coating can be cured by both light and heating. This dual curing method is more flexible and can select the optimal curing method according to actual production conditions, avoiding the limitation that traditional coatings can only be cured by a single method. In addition, in this embodiment, the curing reaction of alicyclic epoxy resin and cationic initiator is usually carried out at a lower temperature and does not produce volatile harmful gases. Compared with ordinary liquid coatings, in this embodiment, the vacuum bonding curing coating has higher environmental protection, reducing pollution to the environment and health threats to operators.

[0017] In some preferred embodiments, the curing coating for vacuum bonding includes two properties: light curing and heat curing; when the curing coating for vacuum bonding applied between the substrate and the diaphragm is light cured, the substrate is a transparent substrate. It should be noted that light curing is a fast and efficient curing method, which is particularly suitable for scenarios where mass production is required in a short time. For transparent substrates, light curing can directly activate cationic photoinitiators through light, prompting alicyclic epoxy resins to cure rapidly, thereby speeding up production. Since the substrate is transparent, light can easily penetrate the substrate and reach the coating layer, so that the entire coating is uniformly cured, ensuring that the diaphragm and the substrate are closely fitted. Light curing not only speeds up production efficiency, but also ensures that the bonding part of the diaphragm and the substrate will not yellow or deteriorate due to long-term light or heat exposure. Since transparent substrates are more easily affected by light, it is particularly important to improve the anti-yellowing performance, which can ensure the aesthetics and long-term use effect of the shell. Light curing can be completed at a lower temperature and solvent-free conditions, reducing pollution to the environment and health hazards to workers, and meeting modern environmental protection and safety production standards.

[0018] In some preferred embodiments, when light curing is adopted, UV light is emitted to the transparent substrate through a UV curing device located on one side of the transparent substrate, and the UV light penetrates the transparent substrate to cure the curing coating for vacuum bonding. It should be noted that the transparent substrate has good light transmittance, and the UV light can smoothly penetrate the substrate and directly act on the coating layer between the substrate and the diaphragm. It should be noted that the UV light penetrates the transparent substrate to cure the curing coating for vacuum bonding, which means that the light can directly reach the coating from the outside without the need for the coating to be exposed to the outside, thereby effectively avoiding the influence of external environmental factors on the curing process, such as dust, humidity, etc., ensuring uniform curing of the coating and enhancing the bonding strength between the diaphragm and the substrate. Further, an optical sensor is integrated on the UV curing device to detect the transparency of the substrate in real time; according to the detected transparency, the intensity, exposure time and irradiation angle of the UV light are automatically adjusted to ensure that substrates with different transparencies obtain the corresponding UV light amount. It should be noted that substrates with different transparencies have a significant effect on the transmittance of UV light. Substrates with higher transparency allow more UV light to penetrate, the coating layer can receive stronger light, and the curing speed is faster. Substrates with lower transparency will block some UV light, so that the coating receives insufficient light, resulting in inadequate curing. Therefore, adjusting the UV light intensity and time based on the transparency of the substrate can ensure that the coating obtains the same curing effect on substrates with different transparencies and improve the uniformity of curing. After the transparency is detected in real time by the optical sensor, the UV curing device can automatically adjust the intensity of the UV light according to the change in transparency. Substrates with high transparency transmit more light, so the UV light intensity can be reduced to avoid over-curing or overheating of the substrate; while substrates with low transparency need to increase the UV light intensity to ensure that enough light can penetrate the substrate to achieve a full curing effect. This automatic adjustment helps to improve production efficiency and save energy. In addition, substrates with different transparencies have different UV light transmittances and require different exposure times. Substrates with high transparency can reach the required light dose in a shorter time, so the exposure time can be shortened to improve production efficiency. Substrates with lower transparency require longer exposure time to ensure that enough UV energy penetrates the substrate for curing. Automatically adjusting the exposure time to ensure that the right amount of UV light is obtained on substrates with different transparencies helps to ensure uniform curing of the coating. Furthermore, a material type database of the substrate is preset, and the material type database includes the substrate material type and the UV light absorption characteristics corresponding to the substrate material type; different UV bands and intensities are configured for the UV curing device; and the UV band and intensity are automatically matched according to the UV light absorption characteristics of the current substrate material type. It should be noted that there are significant differences in the absorption characteristics of UV light by various materials. Some substrates (such as some plastics or resins) can better absorb light energy in a specific UV band, thereby more effectively promoting the curing reaction, while other materials may require different bands to achieve the best effect.If there is no targeted consideration of the absorption characteristics of the material, the use of UV light with a fixed band may result in reduced material curing efficiency or even failure to completely cure. In this embodiment, through the preset material database, the most suitable UV band is selected according to the specific UV absorption characteristics of each material to ensure that the coating between the substrate and the diaphragm can be cured in the best way, thereby reducing unnecessary energy waste and ensuring that each material can be cured at the most suitable wavelength, thereby improving the curing efficiency. Automatically adjusting the UV band and intensity based on the UV absorption characteristics of different materials can make the UV curing process adapt to a variety of different types of substrates. For each substrate, the curing device will select the optimal UV light parameters for curing according to the characteristics of the material, which can ensure the consistency of the curing effect. Both high-light-absorbing materials and low-light-absorbing materials can be fully illuminated and uniformly cured.

[0019] In some preferred embodiments, when the vacuum bonding curing coating applied between the substrate and the diaphragm is thermally cured, the substrate is a transparent substrate or a non-transparent substrate. It should be noted that thermal curing is different from light curing, and it relies on heating rather than UV light for curing. Therefore, for the thermal curing process, whether the substrate is transparent does not affect the curing effect. Regardless of whether the substrate is transparent or non-transparent, the curing coating between the substrate and the diaphragm can be uniformly cured by heating. This flexibility makes thermal curing applicable to a variety of materials, including non-transparent materials such as opaque metals and plastics.

[0020] Embodiment 2 The present embodiment provides a curing coating for vacuum bonding, comprising: an alicyclic epoxy resin, a cationic photoinitiator and a cationic thermal initiator; the weight percentage of the alicyclic epoxy resin is 60-77%, the weight percentage of the cationic photoinitiator is 22-39%, and the weight percentage of the cationic thermal initiator is 0.1-1%.

[0021] It should be generally explained that alicyclic epoxy resin is used in this embodiment, and this type of resin has higher weather resistance and anti-yellowing properties compared with traditional linear epoxy resin. Alicyclic epoxy resin is not easy to turn yellow due to the influence of light or heat in long-term use, thereby maintaining the transparency and aesthetics of the shell. In addition, in this embodiment, the vacuum bonding curing coating contains a cationic photoinitiator and a cationic thermal initiator, which indicates that the coating can be cured by both light and heating. This dual curing method is more flexible and can select the optimal curing method according to actual production conditions, avoiding the limitation that traditional coatings can only be cured by a single method. In addition, in this embodiment, the curing reaction of alicyclic epoxy resin and cationic initiator is usually carried out at a lower temperature and does not produce volatile harmful gases. Compared with ordinary liquid coatings, in this embodiment, the vacuum bonding curing coating has higher environmental protection, reducing pollution to the environment and health threats to operators.

[0022] Embodiment 3 See also Figure 1 This embodiment provides a method for preparing a curing coating for vacuum lamination, comprising the following steps: S101, adding the cationic thermal initiator to the cationic photoinitiator and stirring evenly in the dark to obtain a mixture of the two cationic initiators; S102, adding the mixed two cationic initiators into the alicyclic epoxy resin as a whole and stirring evenly to obtain a cured coating as a whole; S103, vacuum degassing the entire cured coating to obtain the cured coating for vacuum bonding.

[0023] It should be noted that in step S101, the cationic thermal initiator is added to the cationic photoinitiator and stirred evenly in the dark to obtain the two mixed cationic initiators as a whole. Cationic photoinitiators will react or degrade in advance when exposed to light, resulting in reduced activity. Therefore, operating under light-proof conditions can protect the activity of the photoinitiator, ensure that the photoinitiator maintains stability and efficiency during the mixing process, and avoid unexpected light-induced curing reactions during the preparation stage. In addition, before adding the two initiators separately to the epoxy resin, they are first mixed evenly to ensure the uniform distribution of the cationic thermal initiator and the cationic photoinitiator, thereby achieving the best initiation effect in the cured coating, ensuring that the two initiators can play their respective roles in the subsequent curing process, and realizing the flexibility of dual curing of light and heat.

[0024] It should also be noted that in step S102, the two mixed cationic initiators are added to the alicyclic epoxy resin as a whole and stirred evenly to obtain a cured coating as a whole. The alicyclic epoxy resin is the main matrix material, while the cationic photoinitiator and the thermal initiator are the key active ingredients of the curing reaction. Adding the two initiators as a whole to the epoxy resin and stirring them evenly can ensure that the initiators in the coating are fully dispersed in the resin to avoid unevenness. Through the evenly distributed initiators, the light and thermal initiators can simultaneously start the curing reaction under appropriate conditions, achieving the synergistic effect of light curing and thermal curing. This allows the entire coating to achieve a good curing effect under different production conditions (light or heating).

[0025] It should also be noted that in step S103, the entire cured coating is vacuum degassed to obtain the cured coating for vacuum bonding. During the preparation process, bubbles are introduced due to the stirring process. If not treated with vacuum degassing, these bubbles will affect the performance of the coating, such as bonding strength, transparency and uniformity of the coating, during the subsequent curing process. Vacuum degassing is to remove bubbles in the coating to ensure that the final coating surface is smooth and defect-free, and to ensure the reliability of the bonding effect. If the cured coating contains bubbles, the bubbles will diffuse or aggregate during the vacuum bonding process, resulting in local voids or insufficient strength of the coating, which ultimately affects the bonding firmness and appearance quality between the substrate and the diaphragm.

[0026] In some preferred embodiments, the cationic thermal initiator can be selected from sulfonium salts (such as diphenylsulfonium tetrafluoroborate), iodonium salts (such as diphenyliodonium pentafluoroantimonate) or alkyl tungstate salts. Sulfonium salts and iodonium salts have good thermal stability and can release active cations at higher temperatures to start the polymerization reaction of epoxy resin. They can quickly initiate the curing reaction under specific temperature conditions and are suitable as effective initiators in the thermal curing process. These cationic thermal initiators can effectively start the reaction at a relatively low temperature (generally between 80-120°C), and have a fast reaction speed and high curing efficiency. They can accelerate the overall curing process and are particularly suitable for mass production in situations where efficiency requirements are high. These cationic thermal initiators have good compatibility with epoxy resin systems, will not have side reactions with epoxy resins, and can ensure that the system stably releases cations during the curing process to promote the polymerization reaction.

[0027] In some preferred embodiments, the cationic photoinitiator can be selected from iodonium salts (such as diphenyliodonium pentafluoroantimonate), sulfonium salts (such as diphenylsulfonium hexafluorophosphate), aryl sulfonium salts or iron metal salts (such as iron trifluoride complexes). Ionium salts and sulfonium salt initiators have very high light responsiveness, especially in the ultraviolet (UV) band, they can quickly release cations and start the photopolymerization reaction of epoxy resin. This allows the coating to be photocured in a short time, which is suitable for rapid production needs. These cationic photoinitiators have good responsiveness to ultraviolet light of different bands (such as UVA, UVB, etc.) and can adapt to different light source conditions. This characteristic allows the coating system to flexibly select different light sources for curing according to production conditions. The selected cationic photoinitiators should have good light stability and low toxicity to ensure that the coating will not produce harmful byproducts during the photocuring process. Ionium salt initiators have fewer side reactions and better environmental performance, which meets the environmental protection requirements of modern industrial production.

[0028] In some preferred embodiments, the alicyclic epoxy resin can be selected from 3,4-epoxycyclohexanemethyl-3,4-epoxycyclohexanecarboxylate (ERL-4221), bis(3,4-epoxycyclohexylmethyl) adipate (ERL-4299) or epoxymethylcyclohexane (such as Cyclosol 53). Compared with traditional linear epoxy resins, these alicyclic epoxy resins have better weather resistance and anti-yellowing properties, and are particularly suitable for applications exposed to light or high temperature for a long time, such as electronic equipment housings. These alicyclic epoxy resins are not easily yellowed due to light or heat exposure, so the transparency and aesthetics of the appearance after bonding can be guaranteed. These alicyclic epoxy resins have high mechanical strength and toughness, and can improve the overall mechanical properties of vacuum bonding coatings, including tensile strength, bending strength and impact strength. These alicyclic epoxy resins have a faster curing reaction speed, especially under the action of cationic initiators, they can quickly undergo polymerization and achieve the expected mechanical strength.

[0029] When producing the curing coating for vacuum lamination, the following specific implementation methods may be adopted.

[0030] Embodiment 1, the weight percentage of the alicyclic epoxy resin is 60%, the weight percentage of the cationic photoinitiator is 39%, and the weight percentage of the cationic thermal initiator is 1%. Add the cationic thermal initiator to the cationic photoinitiator and stir evenly in the dark to obtain the two mixed cationic initiators as a whole; add the two mixed cationic initiators as a whole to the alicyclic epoxy resin and stir evenly to obtain the cured coating as a whole; vacuum degas the cured coating as a whole to obtain the cured coating for vacuum bonding. In this embodiment, a tensile test can be performed according to the GB / T 2567-2008 standard, and a tensile testing machine is used to measure the various properties of the bonded samples of the substrate and the diaphragm when subjected to force. For example, the tensile strength, tensile elastic modulus, elongation at break, etc. of the bonded sample when subjected to force are measured. The following experimental data and properties of the bonded sample are obtained through the test, specifically: tensile strength 70-80 MPa, tensile elastic modulus 3000-4000 MPa, elongation at break 3-6%. Among them, the tensile strength is 70-80 MPa, which indicates the maximum stress that the laminated sample can withstand when subjected to tensile force. The alicyclic epoxy resin itself has a high mechanical strength, and the high tensile strength indicates that the laminated sample has a strong tensile resistance. The tensile elastic modulus is 3000-4000 MPa, which reflects that the elastic deformation ability of the laminated sample under tensile stress has sufficient rigidity and elastic stability. The application of alicyclic epoxy resin ensures a higher modulus value, which is conducive to ensuring the durability and structural stability of the shell. The elongation at break is the percentage that the laminated sample can be extended before breaking, indicating the ductility or flexibility of the laminated sample. The elongation at break of 3-6% indicates the ductility or flexibility of the laminated sample. The alicyclic epoxy resin can improve ductility to a certain extent, prevent brittle fracture during the lamination process, and help maintain the firm bonding between the diaphragm and the substrate. In addition, in the present embodiment, the bending resistance of the laminated sample can be recorded by testing in accordance with the GB / T 2567-2008 standard by a three-point or four-point bending tester. For example, the bending strength and bending elastic modulus of the bonded sample. The bending strength reflects the maximum stress that the bonded sample can withstand when bent. A bending strength of 130-150 MPa indicates that the bonded sample has a strong bending resistance when bent, ensuring the ability to withstand bending in practical applications and avoiding deformation of the shell after bonding. The bending elastic modulus is used to measure the rigidity of the bonded sample when bent. A bending elastic modulus of 3000-4000 MPa indicates that the coating has good elastic properties after light or heat curing, which is consistent with the characteristics of alicyclic epoxy resins and ensures the shape stability of the shell. In addition, in this embodiment, the impact strength can be measured by an impact testing machine according to GB / T 2567-2008 standard to test the fracture behavior of the bonded sample when impacted. A differential scanning calorimeter (DSC) is used to measure the glass transition temperature of the bonded sample according to IEC 61006 standard.Impact strength reflects the ability of the bonded sample to resist impact or rapid force. An impact strength of 10-20 kJ / m² indicates that the bonded sample will not break easily when subjected to external impact, showing excellent impact resistance, which helps to improve the durability of the shell. The glass transition temperature (DSC) measures the temperature range in which the bonded sample changes from a rigid glass state to a rubber state. A glass transition temperature of 90-110°C indicates that the bonded sample has a higher glass transition temperature, ensuring that the bonded sample maintains structural stability and excellent mechanical properties within the daily use temperature range. Among them, alicyclic epoxy resins have a higher glass transition temperature, ensuring that the bonded sample maintains structural stability and excellent mechanical properties within the daily use temperature range.

[0031] Embodiment 2, the weight percentage of the alicyclic epoxy resin is 77%, the weight percentage of the cationic photoinitiator is 22%, and the weight percentage of the cationic thermal initiator is 1%. The cationic thermal initiator is added to the cationic photoinitiator and stirred evenly in the dark to obtain the two mixed cationic initiators as a whole; the two mixed cationic initiators as a whole are added to the alicyclic epoxy resin and stirred evenly to obtain the cured coating as a whole; the cured coating as a whole is vacuum degassed to obtain the cured coating for vacuum bonding. It should be noted that according to the GB / T 2567-2008 standard, the tensile properties of the substrate and the film bonding sample are tested using a tensile testing machine, including tensile strength, tensile elastic modulus and elongation at break. The experimental data obtained a tensile strength of 85-95MPa, indicating that after increasing the content of the alicyclic epoxy resin, the bonded sample exhibits a higher tensile resistance and can withstand greater tensile stress. The tensile elastic modulus is 3500-4500MPa, indicating that the sample has better rigidity and elastic stability under tensile stress, further improving the structural stability of the bonded sample. The elongation at break is 2.5-5%, indicating that the ductility or flexibility of the sample is slightly reduced due to the increase in the proportion of alicyclic epoxy resin, but it still has sufficient resistance to brittle fracture. The bending properties of the bonded samples were measured using a three-point or four-point bending tester in accordance with the GB / T2567-2008 standard, and the bending strength was 140-160MPa, indicating that the bonded samples showed stronger bending resistance when bent, ensuring better bending resistance in practical applications and avoiding deformation of the shell after bonding. The bending elastic modulus is 3500-4500 MPa, indicating that the increase in the proportion of alicyclic epoxy resin further improves the rigidity and elastic properties of the sample, ensuring the shape stability and durability of the shell. According to the GB / T 2567-2008 standard, the impact strength of the bonded samples was measured by an impact tester, and the impact strength was 12-22 kJ / m², indicating that the bonded samples have higher impact resistance, can better resist external impact, and further improve the durability of the shell. Using a differential scanning calorimeter (DSC), the glass transition temperature of the bonded sample was measured in accordance with the IEC 61006 standard, and the glass transition temperature was 95-115°C, indicating that the sample has excellent structural stability and mechanical properties within the daily use temperature range. The increase in the proportion of alicyclic epoxy resin further improves its heat resistance and ensures the stability of the bonded sample in a high temperature environment. In general, Implementation 2 can significantly improve the mechanical strength and rigidity of the bonded sample by increasing the proportion of alicyclic epoxy resin, especially in terms of tensile strength, flexural strength and glass transition temperature.

[0032] Embodiment 3, the weight percentage of the alicyclic epoxy resin is 77%, the weight percentage of the cationic photoinitiator is 22.9%, and the weight percentage of the cationic thermal initiator is 0.1%. The cationic thermal initiator is added to the cationic photoinitiator and stirred evenly in the dark to obtain the two mixed cationic initiators as a whole; the two mixed cationic initiators as a whole are added to the alicyclic epoxy resin and stirred evenly to obtain the cured coating as a whole; the cured coating as a whole is vacuum degassed to obtain the cured coating for vacuum bonding. It should be noted that according to the GB / T 2567-2008 standard, the tensile properties of the bonded sample are tested, including tensile strength, tensile elastic modulus and elongation at break, and the tensile strength is 80-90MPa, indicating that the proportion of the alicyclic epoxy resin remains high (77%), but the adjustment of the cationic photoinitiator and the thermal initiator slightly reduces the tensile strength of the sample, and still has excellent tensile resistance. The tensile elastic modulus is 3400-4400MPa, indicating that the rigidity and stability of the bonded sample under tensile stress are still excellent. The elongation at break is 3-5%, indicating that the ductility and flexibility of the sample before fracture are at a moderate level, which can effectively prevent brittle fracture. In addition, the bending properties of the bonded samples were tested by a three-point or four-point bending tester, and the bending strength was 135-155MPa, indicating that the samples have sufficient bending resistance and are suitable for occasions requiring certain structural support. The bending elastic modulus is 3300-4300 MPa, indicating that the samples have good elastic properties under bending stress and can maintain shape stability in actual use. According to GB / T 2567-2008 standard, the impact strength of the bonded samples was measured using an impact tester, and the impact strength was 10-18 kJ / m². The impact resistance was slightly reduced, but it still showed a certain ability to resist external impact, meeting the requirements of daily applications. Using a differential scanning calorimeter (DSC), according to the IEC 61006 standard, the glass transition temperature of the bonded samples was measured, and the glass transition temperature was 92-112℃, showing a higher glass transition temperature, ensuring the structural stability of the samples at room temperature and higher temperature ranges. In summary, Embodiment 3 further adjusts the ratio of cationic photoinitiator and thermal initiator to make the curing reaction process more balanced. Although the tensile strength and impact resistance are slightly lower than those of Embodiment 2, the sample still maintains excellent mechanical properties and thermal stability, especially in terms of glass transition temperature and bending properties. This formula is suitable for applications that have high requirements for durability and flexibility, and are sensitive to economic and process requirements.

[0033] Embodiment 4, the weight percentage of the alicyclic epoxy resin is 65%, the weight percentage of the cationic photoinitiator is 34.5%, and the weight percentage of the cationic thermal initiator is 0.5%. The cationic thermal initiator is added to the cationic photoinitiator and stirred evenly in the dark to obtain the two mixed cationic initiators as a whole; the two mixed cationic initiators as a whole are added to the alicyclic epoxy resin and stirred evenly to obtain the cured coating as a whole; the cured coating as a whole is vacuum degassed to obtain the cured coating for vacuum bonding. It should be noted that according to the GB / T 2567-2008 standard, the tensile strength, tensile elastic modulus and elongation at break of the bonded sample are measured using a tensile testing machine, and the tensile strength is 75-85MPa, indicating that the tensile strength is reduced, and the bearing capacity of the sample under the tensile force is slightly reduced, but it still meets the requirements of most practical applications. The tensile elastic modulus is 3100-4000MPa, and the elastic modulus is slightly lower than that of embodiment 3, reflecting that the rigidity of the sample is reduced, but it still maintains a certain stability. The elongation at break is 4-7%, reflecting that the elongation at break is slightly higher than other implementation methods, indicating that the sample has better ductility and flexibility, and is more superior in preventing brittle fracture. The bending properties are measured by a three-point or four-point bending tester, and the bending strength is 120-140MPa, showing a certain decrease, which is suitable for occasions with medium requirements for bending resistance. The bending elastic modulus is 3000-3900 MPa, reflecting that the decrease in the bending elastic modulus is related to the reduction in the proportion of alicyclic epoxy resin in the formula, but the overall performance can still meet the actual application requirements. According to GB / T 2567-2008 standard, the impact strength of the bonded sample is measured by an impact tester, and the impact strength is 12-20 kJ / m², reflecting that the impact strength is well maintained, indicating that the sample has good resistance to external impact and can effectively resist external forces. The glass transition temperature was measured using a differential scanning calorimeter (DSC) according to the IEC 61006 standard, and the glass transition temperature was 85-105°C, which showed that the glass transition temperature was slightly lower, indicating that the stability of the sample at high temperature was reduced, but it could still maintain good mechanical properties within the general use temperature range. In general, Implementation 4 can improve the ductility and flexibility of the sample during the curing process by increasing the proportion of cationic photoinitiator and reducing the proportion of alicyclic epoxy resin, but it has a decrease in tensile strength and rigidity.

[0034] It should be generally explained that alicyclic epoxy resin is used in this embodiment, and this type of resin has higher weather resistance and anti-yellowing properties compared with traditional linear epoxy resin. Alicyclic epoxy resin is not easy to turn yellow due to the influence of light or heat in long-term use, thereby maintaining the transparency and aesthetics of the shell. In addition, in this embodiment, the vacuum bonding curing coating contains a cationic photoinitiator and a cationic thermal initiator, which indicates that the coating can be cured by both light and heating. This dual curing method is more flexible and can select the optimal curing method according to actual production conditions, avoiding the limitation that traditional coatings can only be cured by a single method. In addition, in this embodiment, the curing reaction of alicyclic epoxy resin and cationic initiator is usually carried out at a lower temperature and does not produce volatile harmful gases. Compared with ordinary liquid coatings, in this embodiment, the vacuum bonding curing coating has higher environmental protection, reducing pollution to the environment and health threats to operators.

[0035] In some preferred embodiments, when the cationic thermal initiator is added to the cationic photoinitiator and stirred in the dark, the stirring speed is 1200 rpm and the stirring time is 15-20 minutes; when the two mixed cationic initiators are added to the alicyclic epoxy resin as a whole and stirred, the stirring speed is 1200 rpm and the stirring time is 5 minutes; when the cured coating is vacuum degassed as a whole, the vacuum degassed time is 30 minutes. It should be noted that the cationic thermal initiator and the photoinitiator need to be fully mixed to ensure that they can play their respective roles in the subsequent curing process. The stirring time is set to 15-20 minutes in order to ensure the uniform distribution of the two initiators and avoid the problem of uneven local concentration when the epoxy resin is added later. Too short a stirring time may cause the initiator to fail to be fully mixed, while too long a stirring time may introduce more air and increase the number of bubbles, thereby affecting the subsequent curing process. The stirring time of 15-20 minutes is an appropriate range that can ensure uniform mixing of the initiator. The speed of 1200 rpm is relatively moderate, which can ensure effective mixing while maintaining the stability of the material. If the speed is too low, the mixture may not be fully mixed, resulting in uneven local reaction; while a too high speed may introduce more bubbles, affecting the uniformity of the coating. Therefore, a speed of 1200 rpm can reduce the generation of bubbles while ensuring uniform mixing.

[0036] It should also be noted that when the mixed initiator is added to the alicyclic epoxy resin, the stirring time is set to 5 minutes, the purpose is to quickly and effectively disperse the initiator into the epoxy resin matrix. This is to ensure that the photoinitiator and thermal initiator are evenly distributed in the coating during the final curing process to ensure the curing consistency of the entire coating. When mixing the cationic initiator and the epoxy resin, the time is set to 5 minutes, which is a relatively short time. Compared with the longer stirring time when mixing the initiator, 5 minutes can effectively reduce the introduction of bubbles while ensuring the full mixing of the initiator and the epoxy resin. If the time is too long, there will be more bubbles, increasing the difficulty of subsequent vacuum degassing. The stirring speed continues to be maintained at 1200 rpm, which is a moderate speed that can ensure the full mixing of the initiator and the epoxy resin without introducing too many bubbles due to excessive speed. Excessive speed may cause uneven dispersion, resulting in unsatisfactory mixing effect. Bubbles will inevitably be introduced during the stirring process. If these bubbles are not removed, they will form gaps after curing, affecting the strength and appearance of the coating. 30 minutes of vacuum degassing time can effectively remove bubbles in the coating, especially some larger bubbles and air masses, making the coating more uniform and dense after lamination. If the vacuum degassing time is too short, some bubbles may not be completely eliminated, affecting the transparency, mechanical strength and appearance quality of the coating; at the same time, the residual bubbles may cause structural defects and weakened adhesion during the curing process. Too long degassing time will reduce the activity of the epoxy resin and may affect the final curing effect of the coating. At the same time, long-term degassing may increase the production cycle and reduce production efficiency. Therefore, 30 minutes is an appropriate time to ensure that the bubbles are fully removed and the reaction activity of the coating is guaranteed.

[0037] In some further preferred embodiments, during the stirring process, the viscosity change of the mixture is monitored by a viscosity sensor, and when the mixture reaches a preset viscosity range, the stirring time and stirring speed of the stirrer are automatically adjusted; the viscosity sensor is a rotary viscosity sensor, and the rotary viscosity sensor is installed at the bottom of the stirrer, and the probe of the rotary viscosity sensor is in direct contact with the mixture. It should be noted that although standard parameters are set for the stirring time and stirring speed, in actual applications, different batches of raw materials may have differences in viscosity and mixing difficulty. By real-time monitoring of viscosity and automatically adjusting the stirring time, uniform mixing of initiator and epoxy resin can be ensured, avoiding the inconsistency problem caused by insufficient artificial setting of time or excessive stirring. By automatically adjusting the stirring time, the waiting time in the preparation process can be shortened, the overall efficiency of the production line can be improved, and unnecessary excessive stirring can be avoided.

[0038] In some further preferred embodiments, the vacuum degassing device includes a bubble detection sensor. After the stirrer completes the stirring according to the automatically adjusted stirring speed and stirring time, the bubble detection sensor monitors the number and size of bubbles in the entire solidified coating in real time. When the bubbles are completely eliminated or the set minimum residual bubble level is reached, the vacuum degassing device automatically stops the degassing process. It should be noted that the fixed setting of the degassing time may cause some coatings to end degassing before the bubbles are completely removed, or the bubbles have been eliminated but the unnecessary time is still extended. Through the bubble detection sensor, the vacuum degassing device can intelligently determine the end point of the degassing process, ensure that the bubbles are completely removed, and ensure the uniformity and quality of the coating. Long-term vacuum degassing may cause the properties of some materials to change or excessive water loss, affecting their final performance. By monitoring the bubble state in real time, the damage to the coating performance caused by long-term degassing can be avoided, and the physical properties and structural integrity of the coating can be ensured. It should be noted that in this embodiment, the bubble detection sensor starts working after the stirring is completed, which can save resources and computing power. In this way, the vacuum degassing device only needs to accurately monitor the bubbles in the critical vacuum degassing stage to avoid wasting unnecessary monitoring work during stirring. This improves the efficiency of the equipment while focusing on the critical quality control link in the degassing process. During the stirring process, the bubbles that the sensor may detect are only temporary due to mechanical stirring, and they may dissipate naturally during subsequent mixing or static processing. Therefore, bubble detection during stirring may cause false alarms or misjudgments. Monitoring after stirring is more accurate and can effectively monitor the bubbles remaining in the mixture and degas these bubbles.

[0039] It should be pointed out that the above embodiments are only preferred specific implementation modes of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention. The protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. An electrical equipment housing, characterized in that: The electrical equipment housing includes a substrate and a film with a decorative effect, and the substrate and the film are bonded together under vacuum conditions by a vacuum bonding curing coating; the vacuum bonding curing coating includes: alicyclic epoxy resin, a cationic photoinitiator and a cationic thermal initiator; the weight percentage of the alicyclic epoxy resin is 60-77%, the weight percentage of the cationic photoinitiator is 22-39%, and the weight percentage of the cationic thermal initiator is 0.1-1%.

2. The electrical equipment housing according to claim 1, characterized in that: The curable coating for vacuum bonding has two properties: light curing and heat curing. When the curable coating for vacuum bonding applied between the substrate and the film is light cured, the substrate is a transparent substrate.

3. The electrical equipment housing according to claim 2, characterized in that: When light curing is adopted, UV light is emitted to the transparent substrate through a UV curing device located at one side of the transparent substrate, and the UV light penetrates the transparent substrate to cure the curing coating for vacuum bonding.

4. The electrical equipment housing according to claim 2, characterized in that: When the curable coating for vacuum lamination applied between the substrate and the film is cured by heat, the substrate is a transparent substrate or a non-transparent substrate.

5. A curing coating for vacuum lamination, characterized in that: include: Alicyclic epoxy resin, cationic photoinitiator and cationic thermal initiator; the weight percentage of the alicyclic epoxy resin is 60-77%, the weight percentage of the cationic photoinitiator is 22-39%, and the weight percentage of the cationic thermal initiator is 0.1-1%.

6. A method for preparing a curing coating for vacuum lamination, characterized in that: include: Add the cationic thermal initiator to the cationic photoinitiator and stir evenly in the dark to obtain a mixture of the two cationic initiators; Adding the mixed two cationic initiators into the alicyclic epoxy resin as a whole and stirring evenly to obtain a solidified coating as a whole; The entire cured coating is subjected to vacuum degassing to obtain the cured coating for vacuum lamination.

7. The method for preparing an electrical equipment housing according to claim 6, characterized in that: The weight percentage of the alicyclic epoxy resin is 60%, the weight percentage of the cationic photoinitiator is 39%, and the weight percentage of the cationic thermal initiator is 1%.

8. The method for preparing an electrical equipment housing according to claim 6, characterized in that: The weight percentage of the alicyclic epoxy resin is 77%, the weight percentage of the cationic photoinitiator is 22%, and the weight percentage of the cationic thermal initiator is 1%.

9. The method for preparing an electrical equipment housing according to claim 6, characterized in that: When the cationic thermal initiator is added to the cationic photoinitiator and stirred in the dark, the stirring speed is 1200 rpm and the stirring time is 15-20 minutes; when the two mixed cationic initiators are added to the alicyclic epoxy resin as a whole and stirred, the stirring speed is 1200 rpm and the stirring time is 5 minutes.

10. The method for preparing an electrical equipment housing according to claim 6, characterized in that: When the entire cured coating is subjected to vacuum degassing, the vacuum degassing time is 30 minutes.